1992
DOI: 10.1007/bf00180862
|View full text |Cite
|
Sign up to set email alerts
|

Absolute quantitation of gallium-67 citrate accumulation in the lungs and its importance for the evaluation of disease activity in pulmonary sarcoidosis

Abstract: Our modification of a method for the absolute quantification of gallium-67 uptake in lungs with a scintillation camera and computer is described. The uptake of 67Ga in lungs, expressed in percentage of administered radioactivity, was determined by the transmission-emission method. We proved theoretically and experimentally that a 67Ga planar source could be replaced with a 57Co planar source. The performance of lung perfusion scans allows a more accurate delineation of the regions of interest on gallium scans.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Since Ga is taken into macrophages or epithelioid cells, a Ga scintigram is not positive without granuloma formation. There are some reports that the Ga scintigram is useful for detecting granuloma [23,24] in comparison with other examinations, but in this study HRCT was more sensitive and specific for the early detection of sarcoidosis ( fig. 2).…”
Section: Discussionmentioning
confidence: 63%
“…Since Ga is taken into macrophages or epithelioid cells, a Ga scintigram is not positive without granuloma formation. There are some reports that the Ga scintigram is useful for detecting granuloma [23,24] in comparison with other examinations, but in this study HRCT was more sensitive and specific for the early detection of sarcoidosis ( fig. 2).…”
Section: Discussionmentioning
confidence: 63%
“…31,32 Several computer-aided methods for quantifying pulmonary gallium uptake have been reported for assessing pulmonary disease activity in sarcoidosis. 12,[33][34][35][36][37][38][39] For example, Brantley et al found that parotid gland biopsy yield was marginally higher in those with abnormal gallium parotid uptake. 40 To our knowledge, little research has been done to quantify uptake in the lacrimal gland 10 and no study has correlated biopsy results with the intensity of gallium uptake in the lacrimal region.…”
Section: Discussionmentioning
confidence: 99%
“…Gallium uptake may be considered as a bioassay of the activity of a known inflammatory process (acute versus chronic or quiescent inflammation; response of sepsis to treatment, etc.) (2). Low grade, welldifferentiated tumors often have lower gallium affinity ("false negative"), which is a good prognostic sign (3).…”
Section: Gallium Scanning For Sepsis and Tumormentioning
confidence: 99%